Pemberdayaan Masyarakat Melalui Program Bank Sampah Bissampole Bersinar Di Kelurahan Pallantikang Kecamatan Bantaeng Kabupaten Bantaeng - St. Jumriani; Mahmuddin; Hamriani (Jurnal Berita Sosial, 2024)
The type of research used is qualitative research, this research uses a sociological approach, while the research instrument uses interview guides, writing tools (books and pens), and recording devices (cellphones). After everything was summarized, the researcher carried out data analysis by means of data reduction, data presentation, and drawing conclusions. The results of this research show that forms of community empowerment through the Bissampole waste bank program shine in Pallantikang sub-district, Bantaeng sub-district, Bantaeng district, namely: (1) The community empowerment stage is: (a) Awareness stage, (b) Capability transformation stage. (c) Intellectual and skills improvement stage. (2) Forms of community empowerment are: (a) Assistance in the form of three-wheeled vehicles (viars) to the waste bank management team, (b) Assistance in the form of waste scales to the waste bank management team, (c) Carrying out outreach, (d) Preparing savings books .The contribution of waste banks in community empowerment is: (1) Environmental aspects, this program can increase public awareness of the importance of maintaining the environment so that it looks clean, healthy, neat and comfortable. (2) Economic aspect, the existence of this waste bank can also generate economic value because when people deposit their waste into the waste bank, they will get money that can be used to meet their daily needs. (3) Social aspect, when customers come to the waste bank to deposit their waste, they will meet other customers, thereby creating or building interactive communication with both fellow customers and the waste bank management team.